Prior knowledge and entrepreneurial innovative success - Uwe Cantner; Maximilian Goethner; Andreas Meder (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
This paper is concerned with the relationship between innovative success of entrepreneurs and their prior knowledge at the stage of firm formation. We distinguish between different kinds of experience an entrepreneur can possess and find evidence that the innovative success subsequent to firm formation is enhanced by entrepreneurs prior technological knowledge but not by prior market and organizational knowledge. Moreover we find that prior technological knowledge gathered through embeddedness within a research community has an additionally positive influence on post start-up innovative success. This is a first hint towards the importance of collective innovation activities.
Keywords: L25; O31; Z13; 330; Entrepreneurship; Networks; Prior knowledge; Innovation; Erfolgsfaktor; Unternehmensgründung; Wissen; Technologie; Deutschland